Quest for Better Technology: Case of Brown Coir Fibre Industry in Sri Lanka - K. V. N. N. Jayalath; P. M. E. K. Pathiraja; U. K. Jayasinghe-Mudalige; S. D. J. N. Subasinghe; W. G. P. Weerasinghe (International Coconut Community Journal, 2009)
The purpose of this study was to assess the impact of a number of attributes (a = 23) upon 5 major factors (Labor, Land and Capital, Machine, Technical and Market) that influence a selection of a particular technology to manufacture brown coir fibre in Sri Lanka (i.e. Sri Lankan Drum Pairs, Defibering Machine, D1 Machine). A cross section of owners of fibre mills (n = 30) located in the Kurunegaka, Puttlam and Gampaha districts were selected and a personal interview with each mill owner was carried out with the help of a structured questionnaire from May to June 2008 to collect data. The Semantic Differential Analysis techniques were employed to find the relative strength of the attributes of 5 factors considered in the analysis, where the responses were recorded on a seven-point bipolar scale. The “XLStat” software was used extensively to plot the relationships between the 23 attributes and 3 technologies. The results suggest that all three technologies are negatively perceived by the coir fibre millers on land and capital, and machine subsets. Further millers had negative perception on attributes related to labor subset of Sri Lankan Drum Pair technology. However, they hold the view that high quality of the bristle fibre extracted by this machine is not comparable with that extracted using any other technologies. The millers’ perception on technical and market attributes of the three different technologies was better than on other attributes. The results imply that policymakers should, more specifically, take into account the issues related to capital, machine and labor as they advise coir fibre manufactures about possible technology transfer, in order to avoid potential failures in these markets (i.e. plant-exit) and government policy (i.e. non-compliance).